Development and validation of an instrument to measure nurse educator perceived confidence in clinical teaching. (6th October 2017) - Nguyen, Van N.B.; Forbes, Helen; Mohebbi, Mohammadreza; Duke, Maxine
Abstract: Teaching nursing in clinical environments is considered complex and multi‐faceted. Little is known about the role of the clinical nurse educator, specifically the challenges related to transition from clinician, or in some cases, from newly‐graduated nurse to that of clinical nurse educator, as occurs in developing countries. Confidence in the clinical educator role has been associated with successful transition and the development of role competence. There is currently no valid and reliable instrument to measure clinical nurse educator confidence. This study was conducted to develop and psychometrically test an instrument to measure perceived confidence among clinical nurse educators. A multi‐phase, multi‐setting survey design was used. A total of 468 surveys were distributed, and 363 were returned. Data were analyzed using exploratory and confirmatory factor analyses. The instrument was successfully tested and modified in phase 1, and factorial validity was subsequently confirmed in phase 2. There was strong evidence of internal consistency, reliability, content, and convergent validity of the Clinical Nurse Educator Skill Acquisition Assessment instrument. The resulting instrument is applicable in similar contexts due to its rigorous development and validation process.